Peningkatan Literasi Hukum Ekonomi Syariah Pinjaman Online Ilegal Bagi Organisasi Kepemudaan - Nur Aziz Muslim; Siswahyudianto; Khutbuddin Aibak; Frisna Septian Renaldi; Ria Regita (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This community service project was motivated by the increasing misuse of illegal online lending among youth in Kedungwaru, Tulungagung, driven by low literacy in sharia economic law and limited digital risk awareness. The program focused on strengthening sharia economic legal literacy related to illegal fintech for local youth organizations, which play a strategic role in preventing financial misconduct among young people. The primary objective was to enhance participants’ understanding of illegal online loan characteristics, sharia principles in financial transactions, and digital risk mitigation strategies. The project employed an educational-participatory approach through Focus Group Discussions (FGDs), interactive lectures, case demonstrations, and comprehension assessments. Data were collected through observation, questionnaires, and limited interviews. The results indicate a significant improvement in participants’ understanding of fintech legality, the concepts of riba and gharar within illegal lending practices, and their ability to identify fraudulent loan applications. Participants also demonstrated readiness to act as educational agents within their respective youth communities.